Standardization of micronutrient dosage to improve yield and quality of cocoa (Theobroma cacao L.) grown under coconut ecosystem in Tamil Nadu - Jegadeeswari, V.; Kunikullaya, G. Amitha; Suresh, J. (Journal of Plantation Crops, 2024)
A study on standardization of micronutrient dosage to improve growth, yield and quality of cocoa (Theobroma cacao L.) was carried out at farmer’s field, Anaimalai, Pollachi, Coimbatore district to find out a suitable micronutrient combination for cocoa grown in coconut gardens as intercrop. The experiment was conducted with eight treatments and three replications laid out in Randomized Block Design (RBD). Micro-nutrients used in this experiment were 0.5% ZnSO4, 0.3% FeSO4 and 0.1% Boraxin different combinations. Foliar spray was given thrice, first spray at the time of flowering and consecutive two sprays at 45 days interval to cocoa trees intercropped under coconut plantation. Observations on yield and quality parameters were recorded in cocoa. The pod characters namely pod length (22.2 cm) and pod girth (30.6 cm) were recorded maximum in the treatment combination(ZnSO4 (0.5%) + FeSO4 (0.3%) + Borax (0.1%)). The treatment (FeSO4 (0.3%)) registered maximum pod weight of 256.6 g. Treatments comprising of boron by itself and in combinations was found to improve the bean characters. The highest dry bean yield (2499.93g)per tree was recorded in (Borax (0.1%)).